News brand attribution in distributed environments: Do people know where they get their news? - Kalogeropoulos, A; Fletcher, R; Nielsen, R (SAGE Publications, 2018)
The digital media environment is increasingly characterized by distributed discovery, where media users find content produced by news media via platforms like search engines and social media. Here, we measure whether online news users correctly attribute stories they have accessed to the brands that have produced them. We call this “news brand attribution.” Based on a unique combination of passive tracking followed by surveys served to a panel of users after they had accessed news by identifiable means (direct, search, social) and controlling for demographic and media consumption variables, we find that users are far more likely to correctly attribute a story to a news brand if they accessed it directly rather than via search or social. We discuss the implications of our findings for the business of journalism, for our understanding of source cues in an increasingly distributed media environment and the potential of the novel research design developed.